Validated Spectrophotometric Methods for the Estimation of Ceftriaxone in Pharmaceutical Preparations - Chandra Sekhar, M.; Manohara, Y.N.; Srinivasa Rao , K.; Appala Raju, S. (Asian Journal of Chemistry, 2010)
Three simple and sensitive visible spectrophotometric methods (I, II and III) have been developed for the quantitative estimation of ceftriaxone in bulk drug and pharmaceutical preparations. Method I is based on the diazotization of ceftriaxone with nitrous acid to form a violet coloured chromogen in alkaline conditions with absorption maximum at 559 nm and obeys Beer's law in the concentration range of 50-150 μg/mL. Method II is based on the diazotization of drug with nitrous acid followed by its coupling with 2-naphthol to form reddish violet coloured chromogen with absorption maximum at 554.5 nm and Beer's law is obeyed in the concentration range of 30-150 μg/mL. Method III is based on the oxidation followed by complex formation reaction of ceftriaxone with potassium ferricyanide in presence of ferric chloride to form greenish blue coloured chromogen with absorption maximum at 797 nm and Beer's law is obeyed in the concentration range of 1-5 μg/mL. The results of analysis for the three methods have been validated statistically and by recovery studies. The results obtained with the proposed methods are in good agreement with the labelled amounts when marketed pharmaceutical preparations are analyzed.